Immigrants' return to schooling in Sweden - Martin Nordin (Institute for Labour Market Policy Evaluation (IFAU), 2007)
The aim of this paper is to examine if the returns to immigrants' schooling are lower than the returns to natives' schooling. In addition the paper tries to establish whether immigrants who invest in different amounts of Swedish education also differ in their returns to schooling. The results show that the difference in returns to schooling between immigrants and natives is generally quite small. Moreover, the returns to schooling are considerably higher for immigrants who arrived in Sweden during compulsory school age than for immigrants who arrived in Sweden after compulsory school age. Moreover, immigrants who complete their schooling in Sweden have, in general, much higher returns than immigrants with only foreign schooling.
Keywords: J15; J24; 330; Immigrants; return to schooling; incomes; Migranten; Bildungsertrag; Schweden